Ontological approach and fuzzy modeling to describe objects of living environment - Попик, Надія Вікторівна (Technology audit and production reserves, 2014)
The use of ontologies and mathematical approach using fuzzy models to describe the housing environment using modern information technology is considered in the article. The aim is developing the intelligent system that is designed to assess the quality of residential environment. The determined indices are depicted as ontological system represented using Protégé tool. The work result is developed ontological model of residential environment that can be used to assess the quality of apartments, houses, neighborhoods and districts. The use of modern information technology and the proposed intelligent system will simplify the work of real estate appraisers and consumers at flat choosing.